The effect of citric acid on the phenolic compounds, flavonoids and antioxidant capacity of wheat sprouts - Preciado-Rangel, Pablo; Gaucín-Delgado, Jazmín Monserrat; Salas-Pérez, Lilia; Sánchez Chavez, Esteban; Mendoza-Vllarreal, Rosalinda; Rodríguez Ortiz, Juan Carlos (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2018)
Wheat sprouts are a source of carbohydrates, fiber, vitamins, essential nutrients and bioactive compounds that have been linked to the prevention and treatment of illnesses. The presence of these compounds in wheat sprouts may be increased by means of the application of organic acids during the growth stage. The objective of this investigation was to evaluate the effect of a sprayed application of citric acid (0, 10-2, 10-3, 10-4 and 10-5 M) on the total antioxidant capacity and total content of phenolic compounds and flavonoids in wheat sprouts. A completely randomized design was used, consisting of six repetitions. The results showed that phenolic compounds, flavonoids and antioxidant capacity increased significantly with the application of a 10-2 M foliar spray as compared to the control. As such, the spraying of low concentrations of secondary metabolism-inducing molecules during the sprout development process is a useful and effective method to stimulate the biosynthesis of bioactive phytochemicals and improve the nutraceutical quality of wheat sprouts.